Entrepreneurship Initiatives and Self-Employment Intentions among Undergraduate Students in University of Cross River State, Calabar - AKPAM, Gabriel Odey; EKAETTE, Samuel Okpon; UGBONG, Moses Bekwapu (Ilorin Journal of Education, 2025)
The study examines the influence of entrepreneurship initiatives and self-employment intention among undergraduate students in University of Cross River State. A descriptive survey research design was adopted for the study. The population consists of 1,418 undergraduate students. A multi-stage sampling approach was used to sample 511 students. Questionnaires were employed as the instrument for data collection. The data collected was analysed using simple linear regression. Findings revealed that there is a significant influence of business planning and mentoring mindset on self-employment intention among undergraduate students of University of Cross River State. The study recommended that Business planning skills should be taught to students with adequate practical experience to enable them visualize any venture of their choice with self-employment intention and Mentoring should be emphasized in school curricula to equip students with self-employment intention.”